Critical Discourse Analysis of Norman Fairclough Model on Dedi Mulyadi's Angry Sentences in tirto.id - Isnaeni, Isnaeni; Wahyuni, Sry; Nurhayati, Nurhayati; Sakkir, Geminastiti (ARRUS Journal of Social Sciences and Humanities, 2025)
This study aims to analyze the angry sentences delivered by Dedi Mulyadi in a news article published by tirto.id online media. The discourse analysis uses the Critical Discourse Analysis approach of the Norman Fairclough model. The data obtained from sentence quotations containing Dedi Mulyadi's expressions of anger in a public forum, which were then analyzed qualitatively. The results showed that the language used by Dedi Mulyadi not only reflects the expression of personal emotions, but also contains elements of power and ideology. The sentences are used to control public discourse and assert his position of authority in the face of local identity symbols such as Persikas. This discourse shows the power relations between political elites and civil society, as well as how the media plays a role in reproducing and disseminating ideological meanings to the wider community.